2017
DOI: 10.18775/ijied.1849-7551-7020.2015.35.2007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Female Education in Economic Growth of Pakistan: A Time Series Analysis from 1990-2016

Abstract: Education is an essential factor of economic growth and a fundamental right of every person. No country can attain sustainable economic growth without substantial investment in education. Education improves technical capabilities of exploring new ideas and innovations. It improves the quality of life and leads to collective benefits to individuals and societies. In this study, we investigate the impact of female education on the economic growth of Pakistan by adopting the methodology of the simple Ordinary Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…The outcome of this relationship has caused more female labor force participation in the market and more economic development (Mujahid & Zafar, 2012). The Table 1 below provides the detail of correlation of female education (Hassan, & Rafaz, 2017).…”
Section: Impact On Girl Educationmentioning
confidence: 99%
“…The outcome of this relationship has caused more female labor force participation in the market and more economic development (Mujahid & Zafar, 2012). The Table 1 below provides the detail of correlation of female education (Hassan, & Rafaz, 2017).…”
Section: Impact On Girl Educationmentioning
confidence: 99%
“…It is also driven by the impact of education on improving the techniques and development of new ideas. (Hassan & Rafez, 2017) Therefore, it can be argued that endogenous growth is an endogenous factor that feeds on social and human capital, leaving a direct effect on nationalregional growth and development.…”
Section: Endogenous Growth Theorymentioning
confidence: 99%
“…The study concentrated in primary, secondary and tertiary levels of education and found the existence of a positive link between different levels of education and economic growth in India. Hassan and Rafaz (2017) made use of simple ordinary least squares method to assess the impact of female education on the economic growth of Pakistan for a period covering 1990 to 2016. The result showed that 1% rise in female education, female labor force involvement, education spending and fertility rate give rise to 96% growth in Pakistan GDP.…”
Section: Empirical Reviewmentioning
confidence: 99%